Quantitative Analysis of Lutein from Iraqi Tagetes erecta - Zainab Aziz Ali (Journal of Global Pharma Technology, 2019)
Tagetes erecta is a plant belongs to the genus Tagetes and family Asteraceae. Phytochemical studies show that tagetes erecta leafs and flowers are rich in alkaloids, flavonoids, tannins and essential oils. Lutein which is an oxycarotenoid and phenolic compounds was found to be the major secondary metabolite. [1]The name lutein comes from the Latin word, lutea, meaning yellow. At normal concentrations in food, it is a yellow pigment, but can appear orange or red at high concentration [2].The tetraterpene Lutein and zeaxanthin are found in high concentrations in the macula of the human eye, giving the macula its yellowish color. In fact, the macula also is called the "macula lutea" (from the Latin macula, meaning "spot," and lutea, meaning "yellow") have an important role in reducing the oxidation and reduce the incidence of cataracts. It is believed that lutein and zeaxanthin in the macula block blue light from reaching the underlying structures in the retina, thereby reducing the risk of light-induced oxidative damage that could lead to macular degeneration (AMD) [3]. In this study lutein was isolated from Tagetes erecta by column chromatography. The isolated lutein was identified by TLC, HPTLC. Structure elucidation was performed using UV, FTIR, 1H-NMR and 13C- NMR. The quantity of lutein was measured in the Iraqi plant.Keywords: Tagetes; Lutein; Isolation.